PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X MIPA 5 SMA N 1 PADANG DALAM PEMBELAJARAN SENI RUPA - Febtia Intan Adyatami, Dra. Zubaidah, M.Pd., Drs. Yusron Wikarya, M.Pd. (Universitas Negeri Padang, 2017)
Purpose of his research is to increase the result of student’s study in class X MIPA 5 SMA N 1 Padang in learning visual art through of cooperative learning with JIGSAW strategy. Method of the research that chose by the researcher is classroom action research. Technique of collecting the data is using observation and test. Result of 32 student’s study pre cycle about 45 raise become 80.28 in the first cycle and the second cycle 87.52. In pre cycle, students finished their study about 4 students. In first cycle, students that can finished their study about 18 students. After doing revision in second cycle, student that finished their study about 27 students.Key words: cooperative learning model with JIGSAW strategy and result of student’s learnig